Exploring Sociodemographic and Mental Health Differences Among Constructed Male Victim Severity Profiles - Depraetere, Joke (Journal of interpersonal violence, 2023)
Stigmas and taboos surrounding male sexual violence, stating that men cannot be sexually victimized and would not experience many adverse effects as a result, continue to shroud the issue of male sexual victimization (SV). Male victims, therefore, remain under-recognized in research, policy, and treatment provisions. Furthermore, knowledge regarding male SV is severely compromised by studying male victims in convenience samples with a focus on hands-on forms of sexual violence. Finally, severity of SV is often described using a one-dimensional approach based on presumed severity leading to an oversimplified image. This study addresses these various gaps in scientific research by constructing severity profiles of male SV based on self-reported consequences, prevalence, and co-occurrence of SV. A total of 1,078 male victims were selected from a Belgian nationally representative sample collected between October 2019 and January 2021. Profiles are constructed using latent class analysis. Sociodemographic differences across the profiles are examined through multinomial regression analysis. Finally, differences in current mental health problems across the profiles are assessed. Four distinct male victim profiles are identified: (a) low severity—low victimization (58.3%), (b) medium severity—hands-off victimization (21.4%), (c) medium severity—poly-victimization (13.3%), and (d) high severity—poly-victimization (7.0%). Group comparisons show how male victims in the high-severity class report significantly higher rates of mental health problems such as depression, anxiety, and suicide and/or self-harm. Significant differences in class membership were found for age, occupational status, relationship status, sexual orientation, and financial status. This study provides new insights in the patterns of male SV and highlights the presence of poly-victimization among male victims. Additionally, we point out how the so-called minor forms of SV (i.e., hands-off SV) can have a large effect on male victims. The study ends with suggestions for care and future research.